FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI KADER DALAM KELAS IBU HAMIL DI KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Nafisah, Lu?lu; Sistirani, Colti; Masfiah, Siti (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2016)
ABSTRACTOne of the efforts to improve the health of mothers and children is a prenatal classwhere they can share and discuss any information and knowledge of pregnancy. The percentage of cadres who participated in prenatal class in Sokaraja Subdistrict was 8,5%. The purpose of this study was for knowing the factors related to cadre?s participation of prenatal class in Sokaraja Subdistrict. This study used an analytical observational with crossectional approach. Population was all of cadres in Sokaraja Subdistrict. Samples amount 38 obtained by purposive sampling based on inclusion and exclusion criterion. Data taken by interview with quitionare and used univariate and bivariate with Chi-Square test to analyze. The research results showed that the variables associated with cadre?s participation of prenatal class were knowledge, participation in other organizations, and internal motivation, while the other variable which were attitude, the length of a person to be a cadre, access of infrastructure, the support of community leaders, and support from midwives, have no relationship. As suggestion, cooperation between village and health centers required to hold socialization and training about prenatal class through majelis ta?lim in order to support the cadres to participate in prenatal class.Keywords : Cadre?s Participation, Prenatal Class, Socialization Kesmasindo, Volume 8, Nomor 2, Juli 2016, Hal. 1-14